Reciprocity effects in the trust game - Alexander Smith (Games, 2013)
I use data from a previous experiment for classifying subjects based on their behavior in the trust game. Prior literature defines a 'reciprocity effect' as the tendency for Second Movers to return proportions increasing in the amounts that they receive. In the data that I use, 31% of Second Movers show reciprocity effects, 31% are neutral, and 25% consistently free-ride, indicating that the aggregate reciprocity effect for the sample as a whole is attributable to a minority of the subjects.
Keywords: 330; trust game; reciprocity; strategy method